Quasi-experiments to estimate the economic impact of research infrastructures - Massimo Florio; Paolo Castelnovo (CERN IdeaSquare Journal of Experimental Innovation, 2023)
The paper discusses the application of the quasi-experiment research design to the empirical evaluation of large-scale research infrastructures' socio-economic benefits. Specifically, after introducing the quasi-experimental methodology, it provides an illustrative example in which a quasi-experiment approach is used to assess the technological procurement spillovers of the Italian Space Agency.